High prevalence of modifiable stroke risk factors identified in a pharmacy-based screening programme. Issue 2 (23rd December 2016) - Sandhu, Roopinder K; Dolovich, Lisa; Deif, Bishoy; Barake, Walid; Agarwal, Gina; Grinvalds, Alex; Lim, Ting; Quinn, F Russell; Gladstone, David; Conen, David; Connolly, Stuart J; Healey, Jeff S
Abstract : Background: Population-based screening for atrial fibrillation (AF) is a promising public health strategy to prevent stroke. However, none of the published reports have evaluated comprehensive screening for additional stroke risk factors such as hypertension and diabetes in a pharmacy setting. Methods: The Program for the Identification of 'Actionable' Atrial Fibrillation in the Pharmacy Setting (PIAAF-Pharmacy) screened individuals aged ≥65 years, attending community pharmacies in Canada, who were not receiving oral anticoagulation (OAC). Participants were screened for AF using a hand-held ECG device, had blood pressure (BP) measured, and diabetes risk estimated using the Canadian Diabetes Risk Assessment Questionnaire (CANRISK) questionnaire. 'Actionable' AF was defined as unrecognised or undertreated AF. A 6-week follow-up visit with the family physician was suggested for participants with 'actionable' AF and a scheduled 3-month visit occurred at an AF clinic. Results: During 6 months, 1145 participants were screened at 30 pharmacies. 'Actionable' AF was identified in 2.5% (95% CI 1.7 to 3.6; n=29); of these, 96% were newly diagnosed. Participants with 'actionable AF' had a mean age of 77.2±6.8 years, 58.6% were male and 93.1% had a CHA2 DS2 -VASc score ≥2. A BP>140/90 was found in 54.9% (616/1122) of participants and 44.4% (214/492) were found to be at high risk of diabetes. At 3 months, only 17% of participants were started on OAC, 50% had improved BP and 71% had confirmatory diabetes testing. Conclusions: Integrated stroke screening identifies a high prevalence of individuals who could benefit from stroke prevention therapies but must be coupled with a defined care pathway.